2021
DOI: 10.23950/jcmk/9710
|View full text |Cite
|
Sign up to set email alerts
|

Individuals' coronavirus disease knowledge levels: A cross-sectional survey in eleven countries

Abstract: This descriptive cross-sectional survey determined the individuals' coronavirus disease knowledge levels in eleven countries.Material and methods: This cross-sectional study was conducted with one thousand forty-three (n=1043) individuals between November and December 2020. Data were collected through an online form with questions on coronavirus disease knowledge.Results: This study revealed that the mean score of coronavirus disease knowledge level was 10.50±3.59. The level of knowledge of coronavirus disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Studies have shown that people with neurotic traits have often exhibits worrying related symptoms (APA, 2017;Opayemi et al, 2020), this implies that people with existing fears of environmental degradation might display increasingly emotional instability that is peculiar to both CAS, EWI and neuroticism. Also, having a high score on this trait causes anxiety and preoccupation with apprehensions of negative side effects when confronted climate change hazards (Opayemi et al, 2020;Yıldız et al, 2021). The results suggested that EWI consistently assess patterns of emotional distress (worry).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that people with neurotic traits have often exhibits worrying related symptoms (APA, 2017;Opayemi et al, 2020), this implies that people with existing fears of environmental degradation might display increasingly emotional instability that is peculiar to both CAS, EWI and neuroticism. Also, having a high score on this trait causes anxiety and preoccupation with apprehensions of negative side effects when confronted climate change hazards (Opayemi et al, 2020;Yıldız et al, 2021). The results suggested that EWI consistently assess patterns of emotional distress (worry).…”
Section: Discussionmentioning
confidence: 99%